The Impact Employer Branding on Employee Retention Gen Z: A Systematic Literature Review - Muhammad Naufal Fakhruddin; Intan Ratnawati (LifeSciFi, 2025)
This study examines the relationship between employer branding and employee retention of Generation Z in Indonesia. As younger generations dominate the workforce, organizations face new challenges in attracting and retaining talent. Employer branding, which was originally part of the marketing function, has now evolved into a strategic component in human resource management that plays an important role in shaping employee perceptions, satisfaction and long-term commitment. This study uses the systematic literature review (SLR) method to analyze academic findings related to employer branding practices and their impact on employee behavior. Results show that employer branding elements such as authentic values communication, inclusive organizational culture, and career development opportunities have a significant influence on emotional attachment and retention, especially in Generation Z. In addition, this generation pays close attention to work-life balance, fairness, organizational ethics, and career growth opportunities in choosing a workplace. This study provides practical recommendations for organizations to strengthen employer branding strategies to retain young talent and promote sustainable organizational development.